Analisis Transportasi Laut Indonesia - Ridwan, Agus Salim; Hartini, Sri (Journal of Regional and City Planning, 1997)
Indonesia is an archipelago country with thousand of islands. Sea transportation has an important and strategic function, in particular, the national shipping. It is called ‘Conditio Sinequa Non’ due to its major role from the beginning of Indonesian national development in many aspect of lives: politics, economy, culture, social and defense. All of these aspects would be effective and efficient if sea transportation could realize the functions within itself and act exactly in the way it should be.Sea transportation still does not have the right pattern for its routine operation (i.e, accomplishing its mission functions), particularly because of merely focusing in economic aspect. As the result, an inequitable trips distribution occured. In order to overcome these, we should anticipate appropriate and suitable ways with the hope to prevent our shipment companies and industries from a non-healthy business climate. In return, it will bring positive impact to our social, economy, politic and defence lives.We have to develop a new network of traffic of shipment that could connect every supply and demand points. Based on this, we will be able to arrange new routes in order to get all of people and cargo well distributed including the capability to anticipate all of changes in the distribution pattern that might happen.There are steps to be made in making routes arrangements, but first we have to get origin-destination matrix. Within this matrix we analyze the generation pattern of all dominant ports. After that, we could arrange cargo generation pattern in macro and hierarchy term. The port hierarchy will then determine which ones are going to be the main routes and which are the second routes.In order to make the new proposed routes working more effectively and to assure the continual existing of our national shipping, further study needs to be taken. This study will be about the need for using ‘cobotage’ principle.